2010
DOI: 10.1007/s11695-010-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Sparing Surgical Technique but Not Stoma Size Affects Body Weight Loss in Rodent Model of Gastric Bypass

Abstract: Introduction-Gastric bypass surgery in rats has been shown to mimic the weight loss pattern seen in humans. The aim of this study was to evaluate whether two variations of the technique to create the gastric pouch resulted in a different outcome regarding body weight and food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 34 publications
3
71
0
2
Order By: Relevance
“…First, systematic studies do not indicate a correlation between the size of the gastrojejunal anastomosis and weight loss in RYGB rats (18). Second, rats do not increase prandial drinking which might suggest an attempt to overcome mechanical constraint through food dilution with water.…”
Section: Clinical Effect 2: Change Of Eating Behaviormentioning
confidence: 94%
See 1 more Smart Citation
“…First, systematic studies do not indicate a correlation between the size of the gastrojejunal anastomosis and weight loss in RYGB rats (18). Second, rats do not increase prandial drinking which might suggest an attempt to overcome mechanical constraint through food dilution with water.…”
Section: Clinical Effect 2: Change Of Eating Behaviormentioning
confidence: 94%
“…A recent study has shown that the eating inhibitory effect and subsequent body weight loss after RYGB seem to depend, at least in part, on vagal transmission because both effects were more pronounced when part of the subdiaphragmatic vagal innervation (specifically the paraesophageal neurovascular bundle) was preserved during RYGB surgery (18); the critical nerves may come directly from the intestines because a lesion of the specific vagal innervation of the portal vein and liver had no effect on the RYGB outcome (130). Further, the decreased excitability of vagal efferent neurons in the dorsal motor nucleus of the vagus that resulted from diet-induced obesity could be reversed by RYGB in rats (14); this was accompanied by an improved response of these neurons to CCK and GLP-1.…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
“…15 Briefly, the proximal jejunum was divided 15 cm distal to the pylorus to create a biliopancreatic limb. After identification of the caecum, the ileum was followed proximally to create a common channel of 25 cm.…”
Section: Animalsmentioning
confidence: 99%
“…77 A similar attenuation of RYGBinduced weight loss was observed with transection of the dorsal vagal para-esophageal bundle, which includes the celiac branches. 78 A recent clinical study in a large cohort of patients undergoing RYGB with or without vagotomy found no effect of vagotomy on percent extra weight loss. 79 However, because all these vagal lesions did not differentiate between afferents and efferents, the conclusions are limited and await more selective vagal manipulations such as targeted genetic deletions in mouse models of RYGB.…”
Section: Role Of Microbiota-host Interactionsmentioning
confidence: 97%